2014
DOI: 10.1007/s12028-014-0004-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Prone Positioning Increase Intracranial Pressure? A Retrospective Analysis of Patients with Acute Brain Injury and Acute Respiratory Failure

Abstract: The analyzed data allow a more precise understanding of changes in ICP and oxygenation during prone positioning in patients with acute brain injury and almost normal baseline ICP. Our study shows a moderate, yet significant elevation of ICP during prone positioning. However, the achieved increase of oxygenation by far exceeded the changes in ICP. It is evident that continuous monitoring of cerebral pressure is required in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 17 publications
0
58
0
1
Order By: Relevance
“…In a more recent study conducted by Roth et al (47) a moderate but significant elevation of ICP during prone positioning was demonstrated. However, the oxygenation during and after prone positioning shows a significant improvement and the achieved increase of oxygenation and PbO 2 by far exceeds and the changes in ICP (47). In conclusion, there is no clear evidence to aid intensivists when deciding whether or not proning a patient when there is co-existence of ARDS and TBI; however, it doesn't seem unreasonable to attempt prone ventilation when hypoxemia is refractory to conventional ventilation.…”
Section: Prone Positioningmentioning
confidence: 84%
See 1 more Smart Citation
“…In a more recent study conducted by Roth et al (47) a moderate but significant elevation of ICP during prone positioning was demonstrated. However, the oxygenation during and after prone positioning shows a significant improvement and the achieved increase of oxygenation and PbO 2 by far exceeds and the changes in ICP (47). In conclusion, there is no clear evidence to aid intensivists when deciding whether or not proning a patient when there is co-existence of ARDS and TBI; however, it doesn't seem unreasonable to attempt prone ventilation when hypoxemia is refractory to conventional ventilation.…”
Section: Prone Positioningmentioning
confidence: 84%
“…In their cohort of patients the authors also observed that the ARDS cases of extrapulmonary origin seem to respond better to the prone position, compared with pulmonary ARDS (46). In a more recent study conducted by Roth et al (47) a moderate but significant elevation of ICP during prone positioning was demonstrated. However, the oxygenation during and after prone positioning shows a significant improvement and the achieved increase of oxygenation and PbO 2 by far exceeds and the changes in ICP (47).…”
Section: Prone Positioningmentioning
confidence: 85%
“…Prone positioning during craniotomy could increase intraabdominal pressure and compromise venous return, which could lead to cerebral venous hypertension and increased ICP [13]. Accordingly, we positioned the patient in the supine lateral position with a large cushion under the ipsilateral shoulder, which facilitated head rotation; we then turned the neck, being careful not to press on the jugular vein.…”
Section: Discussionmentioning
confidence: 99%
“…[91][92][93] The limited numbers of studies that have examined the efficacy of prone position in subjects with brain injury have found that prone position causes a slight increase in ICP; however, this is eclipsed by the clear benefit of improved oxygenation. [94][95][96][97][98] One study evaluated P btO 2 in subjects with ARDS and concurrent subarachnoid hemorrhage and showed that prone position was well tolerated and resulted in significant increases in P btO 2 . 94 Although more studies examining the intersection of brain and lung need to be done, the available data suggest that if a ventilatory strategy results in an improved P aO 2 /F IO 2 ratio, the benefits of improved P aO 2 will be reflected in brain tissue oxygen monitoring and improved patient outcome.…”
Section: Lung-protective Strategies and Brain Tissue Oxygenmentioning
confidence: 99%